PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN, DAN KEAMANAN TERHADAP KEPUTUSAN MENGGUNAKAN E-WALLET APLIKASI DANA (STUDI PADA MAHASISWA PRODI PENDIDIKAN EKONOMI TAHUN 2020-2023) - Tuasamu, Rinawati; Kainama, Maryoni S; Dewi, Syahrina Noormala (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2024)
The purpose of this study is to know the Influence of Perceived Benefit, Perceivedof Convenience and Security on the Decision to use the DANA E-walletsApplication among students the Economics Education Study Program in 2020-2023. This research method uses primary data, with the tests carried out beingDescriptive Analysis, Instrument Test (Validity and Reliability), ClassicalAssumption Test (Normality, Multicholineritas, Heterokedasticity, andAutocorrelation), Multiple Linear Regression Test, Hypothesis Test (T Test and FTest), and Coefficient Determination Test. The data used comes fromrespondents' statements distributed via a gform questionnaire with a total of 30respondents from the 2020-2023 Economic Education Study Program and 25statement items. The results of this research show that Perceived Benefit, Perceived of Convenience and Security Influence the Decision to Use the DANAApplication E-wallets.